Utilization pattern of draught bullocks by different categories of farmers in Tamil Nadu - AKILA, N; CHANDER, MAHESH (The Indian Journal of Animal Sciences, 2011)
The extent of dependence of farmers on bullocks, for farming and other activities was assessed in the 7 agro-climatic zones of Tamil Nadu by selecting 1 district from each zone, with the sample of 210 (70 small, 70 medium and 70 large) farmers. The results indicated that 91.43% large farmers and 40% of the medium farmers maintained the animals mainly for their own use. Whereas, the small farmers utilized their bullocks for ploughing in others’ field (28.57%), commercial carting (25.71%) and for both the activities (45.71%), while 35.71% of medium farmers were using their bullocks for commercial carting apart from their own use. The overall average number of days of utilization in agriculture was 36.28 days. The average working days for small farmers were 220.54 days, 156.16 days for medium farmers and 46.61 days for large farmers. The study indicates that still draught bullocks are a main source of farm power for small farmers, to certain extent for medium farmers and for certain operation with large farmers.